Toward a conception of Peruvian wart - Weiss, Pedro (1926)
The Peruvian wart is a disease which mainly involves the reticulo-endothelial system. This comprommiso, which begins at the end of the hematic phase or fever of Carrion, the attachment of the virus in tissue reaches maximun extension during the period preceding the eruption persisted during the beginning of this, to be later reduced verrucous buttons in the territories where they are formed.